2013
DOI: 10.1016/j.jamcollsurg.2013.07.400
|View full text |Cite
|
Sign up to set email alerts
|

The General Surgery Job Market: Analysis of Current Demand for General Surgeons and Their Specialized Skills

Abstract: BACKGROUND The majority of general surgery residents pursue fellowships. However the relative demand for general surgical skills versus more specialization is not understood. Our objective was to describe the current job market for general surgeons and compare the skills required by the market to those of graduating trainees. STUDY DESIGN Positions for board eligible/certified general surgeons in Oregon and Wisconsin from 2011 to 2012 were identified by review of job postings and telephone calls to hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…A recent study in Wisconsin and Oregon estimated that only 34% of available jobs required fellowship training. 32 By this calculus, approximately 40% of graduating residents were unnecessarily pursuing further training after residency. These authors also found that 43% of job postings were for rural jobs, whereas 35% were for nonacademic metropolitan, and 17% for metropolitan academic jobs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Wisconsin and Oregon estimated that only 34% of available jobs required fellowship training. 32 By this calculus, approximately 40% of graduating residents were unnecessarily pursuing further training after residency. These authors also found that 43% of job postings were for rural jobs, whereas 35% were for nonacademic metropolitan, and 17% for metropolitan academic jobs.…”
Section: Discussionmentioning
confidence: 99%
“…However, positions at high‐volume centres are limited and these fellows are faced with the reality of the job market. A recent study conducted in 2013 found that only 30% of general surgery job postings required fellowship training . This shows that the majority of need in the USA is for broad‐based general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in 2013 found that only 30% of general surgery job postings required fellowship training. 6 This shows that the majority of need in the USA is for broad-based general surgery. As over 80% of graduating residents pursue fellowship training after general surgery residency, 2 fellows should be aware that in reality the majority of their practice may not be limited to the area of their subspecialty training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23] Even more compelling, recent research suggests that breast cancer patients and colon cancer patients are more likely to receive standard-of-care surgical treatment from trained subspecialists. [24][25][26] A shortage of 41 000 general surgeons is projected by 2025, 5 but in the face of data like these, perhaps we should worry more about improving the population's access to surgical subspecialists.…”
mentioning
confidence: 99%